Nuevos registros de poblaciones amenazadas de Pilgerodendron uviferum D.Don (Florin) en su límite norte en la Cordillera de la Costa chilena - Soto, Daniel P.; Bannister, Jan R.; Ríos, Andrea I.; Le Quesne, Carlos (Gayana Botánica, 2010)
We describe twelve previously undocumented Pigerodendron uviferum D.Don (Florin) populations outside of protected areas at the northern limit of the Chilean Coast Range (from 39º43’-40º S), extending their northern limits. These small swamp-populations are isolated within a matrix of pastures and exotic forest plantations, and are subject to “chronic” anthropogenic disturbances.